Application of long short-term memory artificial neural networks to forecast water supply and demand in the Lake Chad Basin - Fouotsa Manfouo, Noe Careme (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.